Trauma Intensive Care Unit 'Bouncebacks': Identifying Risk Factors for Unexpected Return Admission to the Intensive Care Unit. Issue 8 (August 2014) - Christmas, A. Britton; Freeman, Elizabeth; Chisolm, Angela; Fischer, Peter E.; Sachdev, Gaurav; Jacobs, David G.; Sing, Ronald F.
Return transfer (RT) to the intensive care unit (ICU) negatively impacts patient outcomes, length of stay (LOS), and hospital costs. This study assesses the most common events necessitating RT in trauma patients. We performed a retrospective chart review of ICU RT from 2004 to 2008. Patient demographics, injuries and injury severity, reason for transfer, LOS, interventions, and outcomes data were collected. Overall, 158 patients required readmission to the ICU. Respiratory insufficiency/ failure (48%) was the most common reason for RT followed by cardiac (16%) and neurological (13%) events. The most commonly associated injuries were traumatic brain injuries (TBIs) (32%), rib fractures (30%), and pulmonary contusions (20%). Initial ICU LOS was 6.6 ± 8 days (range, 1 to 44 days) with 4.4 ± 7.8 ventilator days. Mean floor time before ICU RT was 5.7 ± 6.3 days (range, 0 to 33 days). Forty-nine patients (31%) required intubation and mechanical ventilation on RT. ICU RT incurred an additional ICU LOS of 8 ± 8.5 days (range, 1 to 40 days) and 5.2 ± 7.5 ventilator days. Mortality after a single RT was 10 per cent (n = 16). RT to the ICU most often occurs as a result of respiratory compromise, and patients with TBI are particularly vulnerable. Trauma pulmonary hygiene practices should be evaluated to determine strategies that could decrease RT.